Airflow limitation more than doubles the risk for hospitalization/mortality in patients with heart failure. (March 2019) - Bugajski, Andrew; Frazier, Susan K; Moser, Debra K; Chung, Misook; Lennie, Terry A
Background: Comorbid chronic obstructive pulmonary disease is found in approximately one-third of patients with heart failure. Survival in patients with chronic obstructive pulmonary disease generally decreases as lung function declines. However, the association between lung function, hospitalization and survival is less clear for patients with heart failure. Aim: The purpose of this study was to determine the predictive power of spirometry measures for event-free survival (combined all-cause hospitalization and/or mortality) in patients with heart failure. Methods: In this secondary analysis of data from three prospective, longitudinal studies, we selected patients with a confirmed diagnosis of heart failure who completed airflow limitation assessment using spirometry measures ( n =137): forced vital capacity, forced expiratory volume/second, and forced expiratory volume/second/forced vital capacity. Cox proportional hazards modeling was used to determine the relationship between spirometry and all-cause hospitalization/mortality with and without adjusting for demographic and clinical covariates over a four-year follow-up period. Results: A majority (74%) exhibited some degree of airflow limitation (forced expiratory volume/second<80% predicted value) and 26 (19%) met the spirometric criterion for chronic obstructive pulmonary disease (forced expiratory volume/second/forced vital capacity⩽0.70). Cox proportional hazards regression models compared all-cause hospitalization/mortality between those with and without airflow limitation. Patients with airflow limitation were 2.2 times more likely to be hospitalized or die compared to those without airflow limitations (hazard ratio: 2.20, 95% confidence interval 1.06–4.53, p =0.03). Conclusion: Patients with comorbid heart failure and airflow limitation were at more than double the risk for an event. Spirometric measures may be useful to patients with heart failure, as tailored management of airflow limitation may impact event-free survival.